PENGARUH PENERAPAN STRUKTUR ORGANISASI DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS ORGANISASI PADA PT. ACE JAYA PROTEKSI CABANG PEKANBARU - Rika Susanti; Samsir '; Dewita Suryati Ningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study held in PT. ACE Jaya Proteksi Pekanbaru branch. The aim is to analyze the influence of organizational structure and culture to organizational effectiveness. Population are all employees, consist of 49 employees that selected by cencus method. Data analyzed by using descriptive and multiple linearregression analysis assisted by SPSS 22 for windows. The study reveals that both organizational structure and culture significantly influence organizational effectiveness either partially or simultaneously. Organizational culture has the stronger effect to organizational effectiveness rather than organizational structure. It is recommended to enhance organizational effectiveness by implementing a more appropriate structure and encouraging the stronger implementation of organizational culture.Keywords: Organizational Structure, Culture and Effectiveness